Analisis Framing cnnindonesia.com Dan detik.com Dalam Pemberitaan Konflik Palestina-Israel Pasca Tewasnya Ismail Haniyeh - Utami, Sinta Dwi; Azis, Abdul; Pranawukir, Iswahyu (Jurnal Keislaman, 2024)
The conflict between Palestine and Israel, triggered by Hamas' attack on Israel on October 7, 2023, is still ongoing. Although there were some mediation and negotiations, there was no agreement between Palestine and Israel. On July 31, 2024, Hamas leader Ismail Haniyeh was killed allegedly by Israel. The death of Ismail Haniyeh had some impacts on Palestinian-Israeli peace efforts. This issue attracts media attention, including cnnindonesia.com and detik.com. This research aims to find out the framing of cnnindonesia.com and detik.com in reporting the Palestinian-Israeli conflict, especially after the death of Ismail Haniyeh. Although these two media belong to the same group, Transmedia, each media has a different news construction. Using the framing analysis theory of Zhongdang Pan and Gerald M. Kosicky, this research examines the news published on both media on July 31, 2024. By examining four structural dimensions, namely syntax, script, thematic, and rhetorical, the results of this study show that there are different framing in news construction. A firm pro-Palestinian stance is shown by cnnindonesia.com while detik.com tries to take a more neutral stance. More comprehensive coverage with a global perspective is also presented by cnnindonesia.com while detik.com presents balanced coverage from both the Palestinian and Israeli sides.